Fractalkine (CX3CL1) and Its Receptor CX3CR1 May Contribute to Increased Angiogenesis in Diabetic Placenta. (16th July 2013) - Szukiewicz, Dariusz; Kochanowski, Jan; Pyzlak, Michal; Szewczyk, Grzegorz; Stangret, Aleksandra; Mittal, Tarun Kumar
Abstract : Chemokine CX3CL1 is unique, possessing the ability to act as a dual agent: chemoattractant and adhesive compound. Acting via its sole receptor CX3CR1, CX3CL1 participates in many processes in human placental tissue, including inflammation and angiogenesis. Strongly upregulated by hypoxia and/or inflammation-induced inflammatory cytokines secretion, CX3CL1 may act locally as a key angiogenic factor. Both clinical observations and histopathological studies of the diabetic placenta have confirmed an increased incidence of hypoxia and inflammatory reactions with defective angiogenesis. In this study we examined comparatively (diabetes class C complicated versus normal pregnancy) the correlation between CX3CL1 content in placental tissue, the mean CX3CR1 expression, and density of the network of placental microvessels. A sandwich enzyme immunoassay was applied for CX3CL1 measurement in placental tissue homogenates, whereas quantitative immunohistochemical techniques were used for the assessment of CX3CR1 expression and the microvascular density. Significant differences have been observed for all analyzed parameters between the groups. The mean concentration of CX3CL1 in diabetes was increased and accompanied by augmented placental microvessel density as well as a higher expression of CX3CR1. In conclusion, we suggest involvement of CX3CL1/CX3CR1 signaling pathway in the pathomechanism of placental microvasculature remodeling in diabetes class C.